Effect of physical exercise on metabolism in patients with atrial fibrillation - Wang, Yutong; Weng, Sixian; Xia, Chenxi; Xu, Tao; Song, Xinyang; Wang, Fang (Frontiers in Cardiovascular Medicine, 2024)
Atrial fibrillation (AF), the most prevalent cardiac arrhythmia, is closely linked to metabolic dysfunctions, including obesity, diabetes, and dyslipidemia. These lead to pathological changes in myocardial metabolism and mitochondrial energy metabolism, thereby aggravating AF's incidence and severity. This review introduces the role of metabolic dysfunctions in exacerbating AF, assesses the therapeutic potential of physical exercise and investigates it as a non-pharmacological intervention to alleviate these metabolic disturbances. Evidence suggests that regular physical activity not only enhances metabolic profiles but also reduces the frequency of AF episodes and improves overall cardiovascular health. At the same time, the review emphasizes the need for individualized exercise regimens, individualized to the metabolic and cardiac conditions of each patient to optimize benefits and minimize risks. Additionally, it calls for more basic studies and large-scale clinical trials to establish and refine evidence-based exercise guidelines specific to AF management.